Correlation Levels Of Mercury In The Blood Toward Levels Of Cystatin C Serum Treatment In Two Rural Traditional Gold Kokap Kulon Progo Yogyakarta (International Journal of Scientific Research and Management (IJSRM), 2015)
Traditional gold processing by using mercury (Hg) as binder (amalgamation) can be environmental pollutants and mercury poisoning in humans. Mercury is a toxic substance that causes kidney damage. The research objective was to analyze the correlation levels of mercury in the blood to levels of Cystatin C in serum traditional gold processing characteristics of the respondent’s age, years of service, nutritional status (BMI) and the use of personal protective equipment (PPE). The research was observational with cross sectional approach. Samples are traditional gold processing (the exposed group) and a total of 11 non-processing of gold (unexposed group) amounted to 11 people. Sampling technique is simple random sampling. Data collected through observation, laboratory tests and a questionnaire and analyzed by descriptive and inferential (multiple linear regressions). These results indicate the levels of mercury in the blood of exposed and unexposed groups between <8 ->8 mg /l, the mean blood mercury levels exposed group 63.65ug / l and a group not exposed to 25.56 ug/l (exceeding standards 5-10 g/l). Serum cystatin C levels exposed and unexposed groups between <0.53 ->1.01 mg/L, mean serum levels of Cystatin C groups exposed to 1.07 mg/L and the group not exposed to 1.10 mg/L (beyond the standard 0,53 to 1.01 mg/L). The analysis showed no correlation mercury levels in the blood (p=0.012) and nutritional status (BMI) (p=0.017) on the serum levels of Cystatin C. There is no correlation among age, years of service and use of personal protective equipment (PPE) against Cystatin C serum levels. The conclusion from this study is that there is a correlation between blood mercury levels and nutritional status (BMI) on levels of Cystatin C in serum traditional gold processing, suggested the rotation and shift work arrangements as well as the completeness of the use of personal protective equipment (PPE) to reduce mercury exposure processing traditional gold.